Vertėjas Barboros Mejeraitės knygų rinkinys - Narbutaitė, Gražina (Knygotyra, 1998)
Barbora Mejeraitė (1898-1982), translator and pedagogue, in 1922-1948 worked as a teacher in the provinces, taught languages, social, natural and exact sciences. She had collected a large, multilingual, universal library, used by her relatives, friends, pupils. After the owner’s death, the library was lost, only 39 volumes in Italian, French and German reached the museum "Aušra" in Šiauliai. The article includes their topical analysis, interesting creations or volumes, having been published repeatedly, of famous, titled authors. The books were published by 16 publishing houses in 1863-1935. Some more important French publishing houses, the production of which was owned by the translator are mentioned also. Almost all the preserved books of B. Mejeraitė have got some mark or inscription of their ownership. These seals and autographs belong not only to the translator herself, but also to the former owners, people of means, Italian libraries. This collection of the books gives us some view of the full personal translator’s library and lets us to understand its cultural value.